2009
DOI: 10.1002/cne.22087
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical plasticity in the gonadotropin‐releasing hormone system of the ewe: Seasonal variation in glutamatergic and γ‐aminobutyric acidergic afferents

Abstract: Temperate zone animals time the onset of reproductive events to coincide with specific portions of the sidereal year. Although the neural mechanisms involved remain poorly understood, a marked annual variation in the brain's sensitivity to estradiol negative feedback is thought to mediate many of the changes in neuroendocrine hormone secretion, especially that of the gonadotropin-releasing hormone (GnRH) neurons, via neural afferents. The aim of the present study was to determine whether glutamatergic inputs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 100 publications
0
15
0
1
Order By: Relevance
“…220 Although not in agreement with previous and subsequent studies that found no evidence for vGlut2 protein in GnRH neurons, 35,221 another investigation found that a vGlut2 promoter construct directed expression to a subpopulation of GnRH neurons located in the medial septum of the mouse. 220 Although not in agreement with previous and subsequent studies that found no evidence for vGlut2 protein in GnRH neurons, 35,221 another investigation found that a vGlut2 promoter construct directed expression to a subpopulation of GnRH neurons located in the medial septum of the mouse.…”
Section: Glutamatementioning
confidence: 81%
See 2 more Smart Citations
“…220 Although not in agreement with previous and subsequent studies that found no evidence for vGlut2 protein in GnRH neurons, 35,221 another investigation found that a vGlut2 promoter construct directed expression to a subpopulation of GnRH neurons located in the medial septum of the mouse. 220 Although not in agreement with previous and subsequent studies that found no evidence for vGlut2 protein in GnRH neurons, 35,221 another investigation found that a vGlut2 promoter construct directed expression to a subpopulation of GnRH neurons located in the medial septum of the mouse.…”
Section: Glutamatementioning
confidence: 81%
“…However, it should be noted that not all GnRH neurons exhibit this simple bipolar morphology. 35 Cell filling experiments in transgenic GnRH-green fluorescent protein (GFP) mice have revealed that GnRH neurons exhibit remarkably long dendrites that can extend for over 2000 μm 36 (Figure 11.2(D)). 32 There is also growing appreciation that the dendritic morphology of a GnRH neuron is modifiable; a notable rearrangement of dendritic structure occurs in the mouse around the time of puberty, 33,34 and seasonal differences have also been observed in the sheep.…”
Section: Distribution Of Gnrh Neuron Cell Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was present in primary omission controls, indicating binding of the secondary antibody to these cells. Since we used the VGLUT2 antibody to stain terminals, but not somata, we disregarded this cellular staining (Sergeeva and Jansen, 2009). An antibody to neuronal nucleus specific antigen (NeuN) was used as a neuron specific counterstain (diluted 1:500, Millipore, ABN78).…”
Section: Methodsmentioning
confidence: 99%
“…LR-5 was previously validated for specificity to GnRH1 (48). For the adult mice, GnRH neuronal counts and morphological assessments were performed on all 20 sections rostral (1.2 mm) and all 40 sections caudal (2.4 mm) to the organum vasculosum of the lamina terminalis (OVLT).…”
Section: Gnrh Icc Neuron Count and Morphological Analysismentioning
confidence: 99%